Faktor-Faktor yang Mempengaruhi Minat Lulusan Pesantren untuk Menjadi Guru di Daerah Terpencil - Muhammad Labib (Jurnal Riset Multidisiplin Edukasi, 2025)
The desire to do good must be owned by everyone, teaching activities are noble deeds carried out by noble people and visiting and living in remote areas is a very heavy sacrifice, where most people's desire is to visit cities to achieve a life with complete facilities and luxuries and more average material income. Education inequality in Indonesia is a common task, so that social justice for all Indonesians can be realized, especially in the aspect of education, because by improving education, Indonesia can become a developed country and super power. To realize this, Indonesia must improve from the roots, namely the people in remote areas, because by developing together Indonesia will be stronger. Pesantren is an Islamic educational institution that has a long history in Indonesia, rooted in the tradition of mosque-based education or dormitories. Pesantren not only teaches religious sciences, but also adaptation and innovation to remain relevant to the times and the upbringing of the kyai, especially the founder of Gontor KH Imam Zarkasyi and Wali Songo such as Sunan Giri who assigned his students to a number of regions in the archipelago are concrete examples to spread education throughout the country. This study aims to identify the factors that influence the interest of pesantren graduates to become teachers in remote areas, as well as the efforts made to increase this interest. This research uses a qualitative data analysis method by following the steps: organizing data, making categories, determining themes, and patterns, testing emerging hypotheses using existing data, looking for alternative explanations of the data and writing reports. The results showed that there are several factors that influence the interest of santri who graduated from pesantren to become teachers in remote areas, namely internal factors: motivation and calling, desire to preach, desire to help others and their abilities and expertise. As for external factors, things that foster interest in teaching or serving in remote areas include: support from family and pesantren, information and education about the teaching profession in remote areas, government programs and policies. In order for this to be maximally realized, efforts made to increase the interest of pesantren santri graduates to become teachers in remote areas must be carried out continuously from various parties so that the interest of pesantren santri graduates and the interest of educated people to teach in remote areas can continue to increase.